Managing New-Onset AF - Vinall, Maria (MD Conference Express, 2014)
During this session, experts discussed various approaches to the management of new-onset atrial fibrillation (AF). Specific topics include AF in patients presenting with myocardial infarction, cardioversion therapy, anticoagulation therapy, as well as patients with minimal symptoms.